MAPPING OF RISK FACTORS IN TEENAGERS IN THE AGE RANGE BETWEEN 14 TO 18 YEAR OLD MOTHER OF THE CITY OF AL-CAMARAGIBE (Fiep Bulletin - online, 2014)
The current article refers to the extension project conducted within the College Poet Fabricio Braga municipality of Matrix Camaragibe - AL, as well as in the city of Porto Calvo - AL. Having to map the risk factors in adolescents aged 14-18 years old. Our principal aim of this project pervades the universe mapping itself, we look at issues that justify a sedentary way of life and poor diet. As well as the entertainment options that these municipalities to offer innovated accessible through this northeastern Brazil technological devices. Therefore, this article, this is a quantitative descriptive research, using as a method biometric assessment using the scale, estadiômentro , tape measure and caliper. However, to collect data from students in the age group 14-18 years is of paramount importance for the development and improvement of the current article, it is based on these data that were generated information about the topic discussed, prompting the level of risk participants who subterram biometric evaluation. Then, using resources such as the calculation of BMI and WHR, following guidelines and normality of the World Health Organization.
Keywords: Risk Factors; Body Mass Index; Waist Hip Ratio.